Unified description of BaBar and Belle data on the bottomonia decays [Y(mS) -->Y(nS) pi(+)pi(-)]; Physical Review D; Vol. 92, iss. 3 - Surovtsev Yu. S. Yury Stepanovich; Bydzovsky P.; Gutsche T. Thomas; Kaminski R. Robert; Nagy M. Miroslav; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2015, 2015)
Title screen